Geronimo Stilton. Books 15 & 16 [compact disc, unabridged] - Stilton, Geronimo (Scholastic Audiobooks, 2008)
Geronimo Stilton, which was originally written in Italian, is a tale about a talking mouse that lives in New Mouse City on Mouse Island, where he works as a journalist for The Rodent's Gazette. Included here are adventure books fifteen and sixteen: A Cheese-Colored Camper and The Mona Mousa Code.